ANALYTICAL MODELING OF ORGANIC CONTAMINANTS IN LEACHATE - GONULLU, MT (SAGE PUBLICATIONS LTD, 1994)
Mathematical modelling is a helpful tool for predicting the hazards which arise from contaminants in leachate. These kinds of models are based on exponentially varying leachate concentration with time. In this research, a model for estimating the concentration of organics, measured as Chemical Oxygen Demand (COD), in leachates from solid waste disposal areas is developed. The model contains processes such as dissolution/dilution, mass transfer, substrate utilization, and microbial mass production. The recommended analytical model is compared with experimental data from two laboratory-scale plants. In addition, the variations of model parameters with the governing processes are determined with respect to time. Experimental data from laboratory and field studies in literature is simulated to verify the model. In order to determine some estimated parameters found by trial and error during modelling, multiple regression equations for the values from simulations are created.
Keywords: LANDFILLS; LEACHATE; MATHEMATICAL MODELING; ORGANICS; COD; SEASONAL WASTES; Engineering; Environmental Sciences & Ecology